Disability as a social construct : legislative roots - Liachowitz, Claire H. (University of Pennsylvania Press, 1988)
Wounded soldiers, injured workers, handicapped adults, and physically impaired children have all been affected by legislation that reduces their opportunities to live a functional life. In Disability as a Social Construct, Claire Liachowitz contends that disability is not merely a result of a handicap but can be imposed by society through devaluation and segregation of people who deviate from physical norms. She analyzes pertinent American legislation, primarily from 1770 to 1920, to provide a new perspective on the mechanisms that translate physical defects into social and civil inferiority.
Revision of the author's thesis (Ph. D.)--Bryn Mawr College.
Keywords: People with disabilities -- Legal status, laws, etc. -- United States -- History.; People with disabilities -- United States -- History.; Sociological jurisprudence.; Persons with Disabilities -- legislation & jurisprudence.; Rehabilitation -- history; United States; Sociologie juridique.; Personnes handicapées -- Droit -- États-Unis -- Histoire.; Personnes handicapées -- États-Unis -- Histoire.; LAW -- Disability.; People with disabilities; People with disabilities -- Legal status, laws, etc.; Sociological jurisprudence; Körperbehinderung; Recht; Geschichte; Integration; USA; Rättssociologi.; Personer med funktionsnedsättning.; Historia.; History